Relationship Between Q-Angle, Footprint, and Leg Muscle Strength on Dynamic Balance of Basketball Athletes - Dasih Ayu Wulansari; Binuko Amar Seto; Dayanto Dayanto (Indonesian Journal of Global Health Research, 2025)
Basketball is a sport that requires accuracy in throwing the ball but also requires maximum foot movement, in basketball fast and agile foot movements are required, such as being able to stand and change direction quickly without losing balance, dynamic human foot movements must of course be based on good balance to create fast and powerful movement maneuvers, humans themselves naturally have different anatomical shapes both in length, width and height although still in the same large pattern, one of which is the flat foot shape and also the angle of the femur and tibia bones known as the Q-angle, the shape of the difference will affect the difference in tension produced in performing muscle contractions and also in more complex movements, namely kicking in a moving position such as or dynamic balance in more complex dimensions. This study aims to determine how the relationship between Q-angle, footprint, and leg muscle strength simultaneously affects dynamic balance in basketball athletes. This study uses multiple regression correlation analysis techniques, which are used to obtain a comprehensive picture of the relationship between dependent and independent variables as a whole, either simultaneously or partially. The results of the study obtained 56 research samples, after the analysis prerequisite test was carried out and met the normality, homogeneity and linearity test values, then continued with a hypothesis test which obtained the results that partially in this study obtained information that only muscle strength had a significant relationship to dynamic balance, with a correlation strength value of 0.789 which means it has a strong relationship. While Q-Angle and footrpint partially did not get significant test results. The results of the multiple regression test obtained the formula DB = 54.275 + 0.35QA + 0.141FP + 0.071 MS + e, where the Constant of 54.275 with positive parameters indicates that Q-angle, Footprint, and muscle strength will increase the dynamic balance value with an R Square value of .0702 which means that the three variables contribute 70.2% of the composition of dynamic balance and the rest is influenced by other factors or outside the regression variable equation studied. There is a simultaneous relationship between Q-angle, Footprint, and muscle strength towards dynamic balance.